Excitatory GABA: How a Correct Observation May Turn Out to be an Experimental Artifact - Bregestovski, Piotr; Bernard, Christophe (Frontiers in Pharmacology, 2012)
The concept of an “excitatory/inhibitory switch” of GABA action during development is based on results mainly obtained in brain slices. However, in vivo measurements, as well as observations made in intact in vitro structures, indicate that GABA is inhibitory in rodents at very early neonatal stages. Moreover, providing energy substrates more relevant to the in vivo situation to neonatal brain slices restores the inhibitory action of GABA. These observations question the very concept of depolarizing GABA and suggest that both the “excitatory/inhibitory switch” and the occurrence of Giant Depolarizing Potentials (GDPs) may simply result from cellular injury due to the slicing procedure, leading to energy deficiency and accumulation of intracellular Cl in injured neurons. Brain slices are widely used to investigate basic processes of brain function. Although being a reduced preparation (i.e. there is no blood flow, oxygen levels are non-physiological, most in vivo metabolites are not present in the artificial cerebrospinal fluid (ACSF)) brain slices provide an easier access to cellular phenomena than in vivo models. Many results obtained in vitro (and reproduced by different laboratories) have been verified in vivo, giving ground